An Anguillid lens: how Eels reconnect people and waterways - Gansworth, Kristi Leora; Bowser, Christopher H. (Frontiers in Human Dynamics, 2024)
The population decline of American Eels (Anguilla rostrata) in North America represents multiple crises: ecosystem destruction, industrial impact, forced relocation, cultural disenfranchisement, water degradation, and biodiversity loss. Once a key component of Indigenous societies, trade routes, economies, and ceremonial cycles, today Eels experience migration barriers and habitat degradation stemming from waterway abuse and land use alteration. The development of agricultural and industrial social norms has led to dramatic reductions in Eel populations across North America. Fishery agencies familiar with Eel life cycles often list species as depleted, and disappearance of Eels is well-accepted in all sectors. Related species of Anguillid Eels are in decline globally.Yet, in some areas, American Eels continue to migrate, grow, and even thrive. This article proposes Eel continuity as powerful survivorship in troubled times, a counter-narrative to overwhelming stories of environmental pessimism. Although Eels are often discredited, reviled, and disrespected by Americans and Canadians alike, their contributions to marine and aquatic zones are underestimated and poorly understood. This article employs a reflexive method of dialogue and commentary from two Eel advocates with interdisciplinary training and backgrounds, who envision relational, wisdombased practices that meaningfully integrate Indigenous, community, academic, and other forms of knowledge about Eels and about water.The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.